Fertilizers for Improving the Growth Characteristics and N Uptake of Wild Rorippa indica L. Hiern in Different Soil - Hastin Ernawati Nur Chusnul Chotimah; Akhmat Sajarwan; Ruben Tinting; Antonius Mau; Gusti Irya Ichriani (PLANTA TROPIKA, 2022)
Rorippa indica L. Hiern is a local vegetable that is widely consumed by Dayak’s tribe in Central Kalimantan, Indonesia. It is mostly traditionally cultivated without fertilizers, resulting in low productivity. The research aimed to investigate the effect of fertilizers and soil type on the growth characteristics and N uptake of R. indica. The experiment was arranged in a factorial completely randomized design consisting of two factors with four replications. The first factor was fertilizer application (control, 20 t ha-1 of chicken manure, and 600 kg ha-1 of NPK), and the second was soil type (peat and Ultisol). The results revealed that the interaction of fertilizers and soil type gave a non-significant effect on all variables observed, except N uptake. The application of NPK increased the plant height and number of leaves significantly. Compared to control, the increment was 112.50% and 130.32%, respectively, and chicken manure application increased the dry weight (327.87%), N total (310.16%), and N uptake of plants by 478% in peat soil and 228% in Ultisol. This finding concludes that 20 t ha-1 of chicken manure can be applied to increase the productivity of R. indica.